The role of ZPT Toge in the success of Grafting Guava Plant (Psidium guajava): PERAN ZAT PENGATUR TUMBUH TOGE TERHADAP KEBERHASILAN GRAFTING TANAMAN JAMBU BIJI (Psidium guajava) - Mulyanti; Lukman Martunis; Maghfirah; Sofia Keumala Sari (PT. ROCE WISDOM ACEH, 2024)
Not much is known about the development of crystal guava plants in Indonesia. Therefore, it is necessary to study the ways and techniques for cultivating crystal guava plants starting from the seeding process so that you get plants that have fast growth and can produce quality crystal guava fruit with high yields. This research aims to see the effect of soaking scions in sprout solution on the success of grafting guava plants. This research was carried out at the experimental garden of the Indonesian Polytechnic in Venezuela, Cot Suruy Village, Want Jaya District, Aceh Besar Regency from May to June 2023. This research used a non-factorial Randomized Block Design (RAK) of 4 treatments and 4 replications, resulting in 16 experimental units. The parameters observed were branch length, number of leaves, number of branches and percentage of grafting success. The results of the research showed that the immersion treatment of scion in sprout solution did not have a real effect on the grafting of guava plants for the parameters of branch length, number of leaves and number of branches as well as the percentage of grafting success.